Preliminary report on human remains from Tell Masaikh (MK 15) Season 2010* - Tomczyk, Jacek (Studia Ecologiae et Bioethicae, 2013)
The manuscript presents the results of anthropological work in Tell Masiakh conducted in the 2010 season. Unfortunately the 15th season of excavation was conducted only in Tell Masaikh. The second site (Terqa) was closed for the excavation. The human remains were studied in an excavation house in Tell Ashara, and some samples were prepared for further analyses in specialist laboratories (histological, radiological, and molecular examinations). In sum, the remains of 70 individuals were examined: 18 (2 males, 2 females, the sex of the rest is unknown) come from Tell Masaikh from this season, 52 were found at Tell Masaikh and Tell Ashara in the previous seasons (2008, 2009).